Evaluation And Assessment Of Efl Instruction With An Islamic Perspective - Kalayo Hasibuan Hasibuan; Putri Rama Annisa Annisa; Rahmi Rahmi; Raihan Fahmi Fahmi (Journal of Innovative and Creativity, 2025)
This study discusses the importance of integrating Islamic values ​​in the evaluation and assessment of English as a foreign language (EFL) learning in Indonesian Islamic educational environments. Through a qualitative descriptive approach based on literature studies, this study highlights that EFL evaluation has so far focused on the cognitive aspect, while the affective and spiritual dimensions have not been optimally accommodated. Values ​​such as honesty, responsibility, and manners are very important to be instilled through the evaluation process so that the goals of Islamic education, namely the formation of noble character, can be achieved. In addition, parental involvement and two-way communication between teachers, students, and families are crucial supporting factors in strengthening the synergy of educational character. The results of the analysis indicate the need for the development of holistic and contextual assessment instruments, as well as teacher training to implement evaluation based on Islamic values ​​systematically. This study recommends updating the curriculum and education policies so that EFL learning not only improves language competence, but also forms students with integrity and Islamic morals.